THE IMPLEMENTATION OF THE LEARNING CYCLE MODEL FOR THE STUDENTS’ LEARNING OUTCOMES IN THE RESEARCH METHODOLOGY - Muh. Anas; Moh. Mulyadi Prasetyo (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2020)
Abstract:This study aims to determine the application of the Learning Cycle model to the students’ learning outcomes of the Research Methodology subjects in the Biology Education department at STKIP Pembangunan Indonesia. This research is a quasi-experimental study with a pretest-posttest control group design. The sample used was 30 students of the Biology department at STKIP Pembangunan Indonesia who programmed Research Methodology. The instruments used were observation sheets and 10 numbers of essay questions. The data analysis techniques are the descriptive statistical analysis and the inferential statistical analysis with the independent sample t-test. Based on the inferential analysis using the independent sample t-test where the p-value of 0.020 is smaller than 0.05 (p <0.05), it is found that there is an effect of the Learning Cycle model on the students’ learning outcomes. Based on the findings of the descriptive statistical analysis, it can be concluded that the application of the Learning Cycle model has an effect on the students’ learning outcomes at STKIP Pembangunan Indonesia in the Research Methodology subject with the value range of 85 – 100 of 6 students with the percentage of 20% and the value range of 65 – 84 of 24 students with the percentage of 80%.Abstrak:Penelitian ini bertujuan untuk mengetahui penerapan model pembelajaran Learning Cycle terhadap hasil belajar mata kuliah Metodologi Penelitian mahasiswa Pendidikan Biologi STKIP Pembangunan Indonesia. Penelitian ini merupakan penelitian Quasi Experimental dengan desain penelitian Pretest-Posttest Control Group Design. Sampel yang digunakan adalah 30 mahasiswa jurusan Biologi STKIP Pembangunan Indonesia yang memprogramkan mata kuliah Metodologi Penelitian. Instrumen yang digunakan adalah lembar observasi dan 10 nomor soal esay. Teknik analisis data yang digunakan adalah analisis statistik deskriptif dan analisis statistik inferensial dengan uji Independent Sampel  t-test. Berdasarkan hasil analisis inferensial menggunakan uji Independent Sampel t-test diperoleh nilai p sebesar 0,020 yang lebih kecil dari 0,05 (p<0,05) dengan demikian dapat disimpulkan bahwa ada pengaruh penerapan model pembelajaran Learning Cycle terhadap hasil belajar mahasiswa. Berdasarkan hasil analisis statistic deskriptif dapat disimpulkan bahwa penerapan model pembelajan Learning Cycle mampu meningkatkan hasil belajar mahasiswa STKIP Pembangunan Indonesia pada mata kuliah metodologi penelitian dengan rentang nilai 85 – 100 sebanyak 6 mahasiswa dengan persentase 20% dan rentang nilai 65 – 84 sebanyak 24 mahasiswa dengan persentase 80%.